2000
DOI: 10.1093/oxfordjournals.bja.a013362
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different doses of remifentanil on the cardiovascular response to laryngoscopy and tracheal intubation

Abstract: We have compared three bolus and infusion regimens of remifentanil on the cardiovascular response to laryngoscopy and orotracheal intubation in three groups of 20 ASA I-II female patients, in a randomized, double-blind study. Patients in group 1 received glycopyrolate 200 micrograms i.v. followed by a bolus dose of remifentanil 1 microgram kg-1 over 30 s and an infusion of remifentanil at a rate of 0.5 microgram kg-1 min-1. The other patients received remifentanil 0.5 microgram kg-1 over 30 s and an infusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
3
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 0 publications
4
59
3
1
Order By: Relevance
“…They used the propofol 0.5 mg/kg followed by 10 mg every 10 s until loss of verbal contact. The present results are consistent with the suppression of remifentanil 0.5 μg/kg/min shown by Miyake et al but are not consistent with the report by Hall et al that infusion of remifentanil 0.25 μg/kg/min suppressed the pressure response to tracheal intubation [18]. The reason for the suppression by low-dose remifentanil seems to be the use of 1% isoflurane and 67% nitrous oxide [18].…”
Section: Discussionsupporting
confidence: 72%
“…They used the propofol 0.5 mg/kg followed by 10 mg every 10 s until loss of verbal contact. The present results are consistent with the suppression of remifentanil 0.5 μg/kg/min shown by Miyake et al but are not consistent with the report by Hall et al that infusion of remifentanil 0.25 μg/kg/min suppressed the pressure response to tracheal intubation [18]. The reason for the suppression by low-dose remifentanil seems to be the use of 1% isoflurane and 67% nitrous oxide [18].…”
Section: Discussionsupporting
confidence: 72%
“…However, the shape of the stylet may hinder its removal and cause longer intubation times. In addition, a recent study showed that intubation times with video laryngoscopes can be decreased with proper preparation of the stylet and tracheal tube (7,27 Various studies indicated that laryngoscopy may cause an undesirable increase in blood pressure and heart rate in anesthetized patients (29)(30)(31)(32)(33)(34)(35). Various video laryngoscopes have been studied to elucidate the hemodynamic changes during orotracheal intubation; however, there has been no study comparing the hemodynamic response to orotracheal intubation of the McGrath Series 5 video laryngoscope and the Macintosh laryngoscope (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen minutes later, remifentanil (R) was injected intraperitoneally (low dose; 0.5 µg kg -1 ) to rats in the remifentanil groups [6]. After anaesthesia, each rat was confined in a transparent pliant retention box, which impaired deambulation but left the head and tail free.…”
Section: Methodsmentioning
confidence: 99%